Surya - Temples of India Project Team (Jio Institute, 2024)
This is arguably the oldest sculpture at the shrine, dated by Ambika Dhaka to the eighth century CE. The sculpture significantly precedes the Harshanth Temple, built in the second half of the 10th century. The Harshnath stone inscription records the devotion towards Lord Harsha of an early founding figure of the Chauhan line, Guvaka-I. He was a local chieftain and feudatory of the powerful imperial Pratihara dynasty, who lived roughly during the first quarter of the ninth century CE. The Shaiva association with the hill could have fairly preceded the time of Guvaka, but what can be said with full certainty was the much older Surya association of the hill. The figure carries standard iconographic features of the Sun God like the fully bloomed lotuses in two hands, long tunic, boots and retinue figures in pairs like his companions - Danda and Pingala, his wives and his sons, the Ashvins.